Encapsulation protocol for fecal microbiota transplantation - Sipos, Dávid; Varga, Adorján; Kappéter, Ágnes; Halda-Kiss, Bernadett; Kása, Péter; Pál, Szilárd; Kocsis, Béla; Péterfi, Zoltán (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Clostridioides difficile infections (CDI) continue to pose a challenge for clinicians. Fecal microbiota transplantation (FMT) is an effective treatment option in CDI. Furthermore, recent and ongoing studies suggest potential benefits of FMT in other diseases as well. Methods We would like to present a novel protocol for encapsulation of lyophilized fecal material. Our method provides with better compliance as well as improved flexibility, storage and safety. Results FMT was conducted in 28 patients with an overall success rate of 82,14% using apsules containing lyophilized stool. 16 of patients were given capsules with lessened bacteria counts. The success rate in this group was 93,75%. Discussion The results highlight the still unanswered questions about the mechanism of action and contribute to a wider use of FMT in the clinical praxis and in research.